Mathematical model for determining costs of unsatisfied customers of HoReCa industry - Gheorghe Zaman; Florea Nicoleta Valentina; Constantin Aurelian Ionescu; Dan Marius Coman; Doina Constanța Mihai; Nicoleta Luminita Gudanescu Nicolau (Amfiteatru Economic Journal, 2022)
Customer relationship management (CRM) plays an important role in ensuring the success of companies. Attracting and retaining valuable, satisfied, and loyal customers are important goals of CRM. The aim of the paper is to highlight the crucial role of the relationship between companies and their satisfied customers in achieving long-term performance. Using mathematical, relational, and accounting models, companies could answer the question posed by the research: "How do we reduce the costs of unsatisfied customers and how do we improve the relationship with customers?". The research results show that by implementing these models, only 2 out of 10 restaurants have positive Net Promoter Score (NPS) and Customer Satisfaction Index (CSI), the costs related to unsatisfied customers being high for all other restaurants. The research results show the number of dissatisfied customers and a plan to turn them into satisfied customers and achieve superior performance. By knowing these issues in advance, companies can improve these relationships, increasing customer satisfaction and loyalty and thus improving their economic performance.
Keywords: C40; C55; M31; 330; Customer Relationship Management (CRM); Net Promoter Score (NPS); Customer Satisfaction Index (CSI); satisfied and loyal customers; costs related to dissatisfied customers; HoReCa (hotel; restaurant; and cafe industry)